G279(P) Learning for and through Work in a Neonatal Intensive Care Unit: A Case Study of Regular Doctor-Psychotherapist Sessions. (7th April 2014) - Ponnusamy, V; Behrens, M
Abstract : Introduction: The work environment of neonatal intensive care unit (NICU) provides rich and many opportunities to learn for and through work. The study analyses the role of confidential Doctor-Therapist (DT) group sessions in promoting junior doctors' learning in a stressful workplace. Methods: A case study and a multi method approach was utilised, including information gathering of as much information as possible about the context of the research participants and the workplace, a structured questionnaire with a mix of open and reflective answers from junior doctors and an open interview with NICU psychotherapist. The British Educational Research Association Guidelines have been followed and all data was anonymised. Results: Doctors unanimously agreed that working in NICU provides many opportunities to learn for and through work. The research participants distinguished between formal learning opportunities e.g. time specifically set aside for learning and informal opportunities i.e. work itself and through discussions as a team. Informal learning opportunities scored higher than formal ones. Although reflection is considered as informal, research participants did not agree that self-reflection helps them to learn for work as learning is not 'made explicit' and reflection is not possible at times due to stressful working conditions. All doctors commented positively on the DT sessions and mainly used them to unburden themselves from stressful experiences. The sessions were not seen as learning opportunity, as they were not perceived as set learning time. However, on reflective notes, there were examples of how the DT sessions helped respondents to learn important generic skills and provided some life long learning indirectly. In psychotherapist's view, the DT sessions encouraged doctors to see and understand other's perspectives better by offering confidential space for discussion. Conclusions: DT sessions promote some generic and unique skills as defined by RCPCH for long term use. Doctors felt that the DT group sessions helped to relieve their stress and hence enjoy work better. These meetings are an effective way to manage the emotional stress at work and promote conditions which allow learning through and for work. A more detailed study, however, in an ethnographic model would help to address various other factors in a complex setting.